Molecular dynamics study on growth of carbon dioxide and methane hydrate from a seed crystal - Nakate, Prajakta; Ghosh, Bappa; Das, Subhadip; Roy, Sudip; Kumar, Rajnish (Chinese Journal of Chemical Engineering, 2019)
In the current work, molecular dynamics simulation is employed to understand the intrinsic growth of carbon dioxide and methane hydrate starting from a seed crystal of methane and carbon dioxide respectively. This comparison was carried out because it has relevance to the recovery of methane gas from natural gas hydrate reservoirs by simultaneously sequestering a greenhouse gas like CO2. The seed crystal of carbon dioxide and methane hydrate was allowed to grow from a super-saturated mixture of carbon dioxide or methane molecules in water respectively. Two different concentrations (1:6 and 1:8.5) of CO2/CH4 molecules per water molecule were chosen based on gas-water composition in hydrate phase. The molecular level growth as a function of time was investigated by all atomistic molecular dynamics simulation under suitable temperature and pressure range which was well above the hydrate stability zone to ensure significantly faster growth kinetics. The concentration of CO2 molecules in water played a significant role in growth kinetics, and it was observed that maximizing the CO2 concentration in the aqueous phase may not result in faster growth of CO2 hydrate. On the contrary, methane hydrate growth was independent of methane molecule concentration in the aqueous phase. We have validated our results by performing experimental work on carbon dioxide hydrate where it was seen that under conditions appropriate for liquid CO2, the growth for carbon dioxide hydrate was very slow in the beginning. (C) 2019 The Chemical Industry and Engineering Society of China, and Chemical Industry Press Co., Ltd. All rights reserved.
Keywords: Cage dynamics; CH4 recovery; CO2 sequestration; F-4 order parameter; kinetics; Natural gas hydrate; Thermodynamics